Mengukur Niat Penggunaan Aplikasi Digital Korlantas dengan Model UTAUT - Dedy Ari Purnomo; Theofilus Alexander Rumkeny; Yekti Asmoro Kanthi (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2026)
This study aims to analyze the factors influencing the intention to use and usage behavior of the Digital Korlantas Polri application by employing the Unified Theory of Acceptance and Use of Technology (UTAUT) approach. A quantitative method with explanatory research was applied, involving 100 respondents who were users of the Digital Korlantas application selected through purposive sampling. The research instrument consisted of questionnaires that had been tested for validity and reliability. Path analysis was used to examine the relationships among variables. The findings indicate that Performance Expectancy, Social Influence, and Facilitating Conditions significantly influence Behavioral Intention, while Effort Expectancy has no significant effect. Furthermore, Facilitating Conditions and Behavioral Intention significantly affect Use Behavior. These results suggest that perceived usefulness, social support, availability of supporting facilities, and accessibility play important roles in increasing users’ intentions and actual usage of the Digital Korlantas Polri application. This study is expected to provide valuable insights for developers and relevant stakeholders in improving the quality and effectiveness of digital public service applications.